Noise Reduction: The Screening Value of Qui Tam - Anthony J. Casey; Anthony Niblett (Washington University Law Review, 2014)
Whistle-blowing mechanisms have long been recognized and used as tools to encourage the revelation of hidden information. The information sought is often evidence of otherwise undetectable fraud. An effective mechanism will be one that best deters such fraud. To do this, the mechanism needs to produce high-quality information that is not otherwise lost in the noise of low-quality information. In this paper, we present a model to explore how the use of a court-centric qui tam mechanism as opposed to an agency-driven mechanism can improve whistle-blowing along these dimensions. We compare two leading mechanisms that have been implemented in high-profile federal statutes. The first is the court-centric qui tam mechanism embodied in the False Claims Act. The second is the agency-centric system enacted as part of the Dodd Frank Act. The model demonstrates that the qui tam mechanism—which allows whistleblowers to bring a lawsuit on behalf of the government—produces a separating equilibrium by imposing a private, loss contingent cost commitment on whistleblowers. When whistleblowers possess private information, the cost commitment screens out low-quality information while maintaining the incentives for high-quality information and lawsuits. In turn, enforcement and deterrence are improved. Counterintuitively, then, increasing costs and lowering rewards for whistleblowers can often lead to better enforcement and less fraud. We conclude by exploring applications of this model and the resulting insights for other areas of private information and third-party enforcement mechanisms.
Keywords: qui tam; whistle blowing; False Claims Act; Dodd Frank Act; incentives